PENGARUH PENERAPAN REWARD AND PUNISHMENT TERHADAP HASIL BELAJAR DRIBBLE BOLA BASKET (STUDI PADA SISWA KELAS IX SMP NEGERI 16 SURABAYA TAHUN AJARAN 2012/2013) - ARI DWIANTORO, GANANG (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In Junior High School have material of bigball game, one of which is basketball game. Basketball is a game of requires movement intensity of very high, so that the student movement is more and better for fitness. In basketball game there are various basic techniques, such as dribble, passing, shooting, footwork. Because of this, material of basketball, one of which is dribble expected to support or achieves learning objectives. The purpose of this research is to get overall picture of activities implementation of reward and punishment to the ability student in learning materials of dribble of basketball in physical education at 16 Junior High School of Surabaya. After the research during 4 weeks were divided into 4 times  meets, for experiment groups nor control groups. Researcher can concluded that to gift extrinsic motivation to be in the form of reward and punishment turned of to give significant increasen to students of experiment groups 13,20% and students of control groups 1,41%. It’s proved that use of reward and punishment gift significant influence to the dribble result of basketball to experiment groups than control groups. Keywords : Reward and punishment, result, dribble. basketball.